Integration of Sustainable Development Goals in Islamic Teaching Materials in Higher Education - Nasrudin, Ega; Anwar, Saepul; Suresman, Edi; Rahmi, Utami Qonita; Hidayatulloh, Deden Syarif; Ahmad Lokman, Fatimah Ezzahrah binti (Pascasarjana Universitas KH. Abdul Chalim, 2025)
This research aims to analyze the integration of Sustainable Development Goals (SDGs) in Islamic teaching materials in higher education. The research method used is a case study design. Data were collected through observations, interviews, and documentation studies of existing Islamic teaching materials. The data analysis process was carried out through data reduction, data presentation, and conclusion drawing using FGD (Focus Group Discussion) technique. The results showed that the Islamic Religion course integrated various dimensions of the SDGs in the teaching materials. The social inclusion dimension proved to be the most dominant dimension, found in every chapter of Islamic Religion teaching materials. In contrast, the dimensions of environmental protection and economic growth tend to have less representation, found in only nine chapters of the entire teaching material. These findings are expected to be taken into consideration for the government in formulating regulations for the preparation of teaching materials that support the achievement of SDGs through the education sector. This research also emphasizes the importance of SDGs integration in higher education. The researcher recommends that similar studies be conducted by expanding the scope of locations, not only limited to one university.